The History of the Devil - Flusser, Vilem, 1920-1991 (Book collections on Project MUSE., 2014)
In 1939, a young Vilem Flusser faced the Nazi invasion of his hometown of Prague. He escaped with his wife to Brazil, taking with him only two books: a small Jewish prayer book and Goethe's Faust. Twenty-six years later, in 1965, Flusser would publish The History of the Devil, and it is the essence of those two books that haunts his own. From that time his life as a philosopher was born. While Flusser would later garner attention in Europe and elsewhere as a thinker of media culture, The History of the Devil is considered by many to be his first significant work, containing nascent forms of t.